Implementing a Spontaneous Social Network for Managing Ubiquitous Interactions - Zaupa, Dante; Costa, Cristiano; Silva, Jéssica; Barbosa, Jorge; Yamin, Adenauer (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
The widespread of mobile devices has allowed people to have access to social networks and the variety of services wherever they are and whenever they want. In this scope, the idea of creating spontaneous social networks allow the interaction among users through the creation of mechanisms of communication and sharing services in specific places. In this sense, this article presents a model of a spontaneous social network based in the user's current location. The proposal, which is called Mingle, allows users to interact, access and offer services related to their current location, preferably through their mobile devices. A prototype was developed, composed of two components, an Android client and a server to manage the spontaneous social network. Based on the prototype, two evaluations were conducted. The first one was related to the mobile client and is based on a scenario. The second evaluation regards the server, and assesses its performance. The results are encouraging and show good potential for Mingle use and application.